A Century of Geneticists : Mutation to Medicine - Dronamraju, Krishna; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Genetics, like all scientific disciplines, is a human endeavor. Thus, the lives of geneticists - their friendships, colleagues and associations - play an important role in the historical development of the science. This book summarizes the history of genetics by reviewing the lives of the prominent and influential researchers beginning with the earliest and simplest branches of genetics (studies of inheritance and mutation) and ending with the human genome project - the pinnacle of genetics research of the 20th century. Key selling features: Summarizes the lives of important genetics researchers Reviews the development of important foundational concepts Highlights the way new technologies and methods have advanced the study of genetics Explores the influence of genetics in other biomedical fields Avoids simplistic chronological summary of genetics.
Population Genetics and Evolution. Mutation Research. Cytogenetics. Biochemical genetics. Molecular biology. Immunogenetics. Behavior Genetics. Quantitative Genetics . Human and Medical Genetics. The Human Genome Project.
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Life Sciences / Biology / Molecular Biology; MEDICAL / Genetics; Geneticists -- History -- 20th century; Genetics -- Research -- History; Geneticists; Electronic books